Poopendous! : the inside scoop on every type and use of poop! - Bennett, Artie (Blue Apple Books, 2012)
"Rhyming couplets feature Professor Poopdeck and two young friends as he takes them on a type of poop safari. Words for poop (i.e. guano, number two, ca-ca), its forms and styles (cubes, tubular, wet and dry), and myriad of uses (i.e. souvenirs, a means of tracking and marking, housing insulation, food, fertilizer, fuel) are all conveyed with humor and a certain demand for respect"--